Effective bioremediation of petroleum‐contaminated saline soil using halotolerant Bacillus strains isolated from the Persian Gulf. (26th October 2022) - Ghaedrahmat, Zeinab; Ghafari, Shokouh; Almasi, Halime; Baboli, Zeynab; Neisi, Abdolkazem
Abstract: A consortium isolated from the Persian Gulf is evaluated for its ability to bioremediate petroleum‐contaminated soils. The soil sample was collected from oil fields of South Western Iran. The crude oil concentrations were set to 1000–10, 000 mg/kg, and the sodium chloride concentration was set to 0.5%, 1%, 1.5%, 2%, and 2.5%. Operational parameters including volume (2–20 ml) and soil moisture (25%, 50%, and 100%) were studied consecutively according to one factor at the time of experimental design. A total number of eight different isolates capable of degrading crude oil were isolated from hydrocarbon‐contaminated sites (KL1–KL8). The removal efficiency of Total petroleom hydrocarbons (TPH) with an initial concentration of 1000 mg/kg for numbers of bacterial cells per gram soil of 2, 10, and 20 CFU/g was 20.9%, 45%, and 60%, respectively. The removal efficiency of TPHs (initial concentration of 1000 mg/kg) at the end of fifth week for salinity amounts of 0.5%, 1%, 1.5%, 2%, and 2.5% was 10.87%, 22.4%, 25.7%, 68.6%, and 60.5%, respectively. The TPHs biodegradation efficiencies at different soil/water ratios of 25%, 50%, and 100% (slurry) were 12%, 28.7%, and 60.8%, respectively. In sunflowers, there was no statistically significant difference in seed germination for different levels of soil pollution ( p > 0.05). The results of the current work suggest that this process is a viable and efficient method for remediating contaminated sites. To enhance the removal results in real soil, a scale‐up study should also be conducted.